The use of nucleic acid hybridization to detect human coronaviruses - Myint, S. (Arch Virol, 1989)
We have applied an RNA: RNA hybridization test for the detection of human coronavirus 229E. This test is undergoing further development but already allows a diagnosis of HCV 229E infection within 48 hours.